Prevenção em diabetes: efeitos do treino de automonitoração na redução de fatores de risco - CASSEB, Mariene da Silva (Universidade Federal do Pará, 2011)
Data from the Brasilian Society for Diabetes show the rapid growth of diabetes mellitus over the population and the great majority of bearers are not aware of the diagnosis. Analysis of behavior applied to health matches the proposal of the World Health Organization which places priority on environment and behavior variables to prevent and manage chronical conditions and has carried out many studies with focus on adherence of patients to the treatment and on the reduction of harm caused by chronic deseases. However, cut-off or reduction of future costs has become indispensable as to people under risk factors such as overweight, family history, sedentariness and inadequate nutrition. On the other hand, studies indicate that the training on automonitoring can prove to be effective on the acquisition and maintaining of behaviors that promote health and reduce the incidence of illnesses. Bases on the constructional model, the objective of this study was to verify by means of case study, the effects of a training on automonitoring on the construction and amplification of preventive behaviors of four individuals with diabetes family history, inadequate nutrition and sedentariness, sons of patients being attended by the Attention to Diabetes Bearer Program at Bettina Ferro de Souza Campus Hospital. Participants were distributed over two conditions: two on Training Condition (TC) and two on Non-Training Condition (NTC). Home visits were carried out for investigation of socio-demographic data, Base Lines 1 and 2 of nutritional behavior and of physical activity, intervention with the CT participants, fortnightly interview with the CNT participants and final interview. The results show significant changes concerning the acquisition and amplification of healthier nutritional habits and physical activities by CT participants and point out few changes on the acquisition and amplification of these habits by CNT participants. The discussion about the results covers aspects that indicate the acquisition of preventive habits, relating them to the literature used and at the end a general conclusion is draw over the accomplishment of this study.